Disparate Seasonal Nitrate Export From Nested Heterogeneous Subcatchments Revealed With StorAge Selection Functions. Issue 3 (11th March 2022) - Nguyen, Tam V.; Kumar, Rohini; Musolff, Andreas; Lutz, Stefanie R.; Sarrazin, Fanny; Attinger, Sabine; Fleckenstein, Jan H.
Abstract: Understanding catchment controls on catchment solute export is a prerequisite for water quality management. StorAge Selection (SAS) functions encapsulate essential information about catchment functioning in terms of discharge selection preference and solute export dynamics. However, they lack information on the spatial origin of solutes when applied at the catchment scale, thereby limiting our understanding of the internal (subcatchment) functioning. Here, we parameterized SAS functions in a spatially explicit way to understand the internal catchment responses and transport dynamics of reactive dissolved nitrate (N‐NO3 ). The model was applied in a nested mesoscale catchment (457 km 2 ), consisting of a mountainous partly forested, partly agricultural subcatchment, a middle‐reach forested subcatchment, and a lowland agricultural subcatchment. The model captured flow and nitrate concentration dynamics not only at the catchment outlet but also at internal gauging stations. Results reveal disparate subsurface mixing dynamics and nitrate export among headwater and lowland subcatchments. The headwater subcatchment has high seasonal variation in subsurface mixing schemes and younger water in discharge, while the lowland subcatchment has less pronounced seasonality in subsurface mixing and much older water in discharge. Consequently, nitrate concentration in discharge from the headwater subcatchment shows strong seasonality, whereas that from the lowland subcatchment is stable in time. The temporally varying responses of headwater and lowland subcatchments alternate the dominant contribution to nitrate export in high and low‐flow periods between subcatchments. Overall, our results demonstrate that the spatially explicit SAS modeling provides useful information about internal catchment functioning, helping to develop or evaluate spatial management practices. Key Points: We introduce a novel spatially varying StorAge Selection (SAS)‐based model to explore nitrate export from nested subcatchments with heterogeneous settings Age selection preference for discharge, transit times of discharge, and nitrate export dynamics varied spatially among subcatchments Contrasting SAS functions between subcatchments seasonally shift the dominant source contributions to overall catchment nitrate export